Nicotinamide mononucleotide adenylyltransferase of Trypanosoma cruzi (TcNMNAT): a cytosol protein target for serine kinases - Sánchez-Lancheros, Diana Milena (Mem Inst Oswaldo Cruz, 2016)
Nicotinamide/nicotinate adenine dinucleotide (NAD+/NaAD) performs essential functions in cell metabolism and energy production due to its redox properties. The nicotinamide/nicotinate mononucleotide adenylyltransferase (NMNAT, EC 2.7.7.1/18) enzyme catalyses the key step in the biosynthesis of NAD+. Previously, the enzyme NMNAT was identified in Trypanosoma cruzi (TcNMNAT), a pathogenic agent with epidemiological importance in Latin America. To continue with the functional characterisation of this enzyme, its subcellular location and its possible post-translational modifications were examined in this study. For this, polyclonal antibodies were generated in mice, with soluble and denatured recombinant protein being used to detect the parasite’s NMNAT. Immunodetection assays were performed on whole extracts of T. cruzi, and an approximation of its intracellular location was determined using confocal microscopy on wild and transgenic parasites, which revealed the cytosol distribution patterns. This localisation occurs according to the needs of the dinucleotides that exist in this compartment. Additionally, a bioinformatics study was performed as a first approach to establish the post-translational modifications of the enzyme. Possible phosphorylation events were experimentally analysed by western blot, highlighting TcNMNAT as a potential target for serine kinases.